Analisis Psiko-Sosial Perilaku Negatif Santri (Bullying, Kekerasan Pada Guru, dan Pergaulan Bebas) Di Lingkungan Pesantren Babun Najah Ulee Kareng Banda Aceh - Nurmila, Nurmila; Syauky, Ahmad; Jannah, Miftahul (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
The phenomenon of negative behavior among students (santri) in Islamic boarding schools (pesantren), such as bullying, violence against teachers, and promiscuity, has become an increasing concern in Islamic education. Pesantren, traditionally regarded as institutions of moral and spiritual development, are now facing complex psychosocial challenges among their students. This study aims to analyze the psychological and social factors that underlie deviant behaviors among santri. The research employs a qualitative-descriptive method using a case study approach in several pesantren across Indonesia. Data were collected through observation, in-depth interviews with students, teachers, and caretakers, as well as document analysis. The findings reveal that negative behaviors are influenced by family background, peer group dynamics, weak supervision, and the lack of psychological-based educational approaches within pesantren. Violence against teachers often stems from imbalanced power relations, while promiscuity arises from exposure to social media and inadequate value-based control. In conclusion, a holistic educational approach grounded in psychology and Islamic values needs to be strengthened to address these issues both preventively and rehabilitatively.